2000
DOI: 10.4049/jimmunol.165.4.2258
|View full text |Cite|
|
Sign up to set email alerts
|

Monocyte Tissue Factor Induction by Activation of β2-Glycoprotein-I-Specific T Lymphocytes Is Associated with Thrombosis and Fetal Loss in Patients with Antiphospholipid Antibodies

Abstract: Antiphospholipid (aPL) syndrome (APS) is characterized by thromboembolic events, thrombocytopenia, or recurrent miscarriage associated with aPL Abs with specificity for β2-glycoprotein-I (β2GPI). We recently reported that at least 44% of patients with the APS possess circulating type 1 (Th1) CD4+ T cells that proliferate and secrete IFN-γ when stimulated with β2GPI in vitro. In this study, we show that stimulation of PBMCs from 20 APS patients with β2GPI induced substantial monocyte tissue factor (TF) (80 ± 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…However, clinical manifestations of APS do not occur in patients with these infectious diseases. Thus, anti-b2-GPI antibodies were detected in patients with APS, but not in patients with those infectious diseases (32). The main difference appears to be an absolute requirement for b2-GPI, a plasma protein, in detection of antiphospholipid antibodies in APS (29,30).…”
Section: Discussionmentioning
confidence: 95%
“…However, clinical manifestations of APS do not occur in patients with these infectious diseases. Thus, anti-b2-GPI antibodies were detected in patients with APS, but not in patients with those infectious diseases (32). The main difference appears to be an absolute requirement for b2-GPI, a plasma protein, in detection of antiphospholipid antibodies in APS (29,30).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, circulating monocytes of patients with primary APS display tissue factor overexpression that may contribute to the prothrombotic state [27]. Stimulation of peripheral blood mononuclear cells of these patients with β 2 ‐GPI induces substantial monocyte tissue factor, which was shown to be dose‐dependent and requiring CD4+ T lymphocytes and class II MHC molecules to be expressed [28]. These findings suggested that patients with APS may have chronic stimulation of β 2 ‐GPI‐specific T lymphocytes which leads to persistently high monocyte tissue factor expression and consequently to a prothrombotic diathesis [28].…”
Section: Discussionmentioning
confidence: 99%
“…97 Stimulation of monocytes from aPL syndrome patients with ␤ 2 GPI induced substantial monocyte tissue factor, whereas no induction was observed with cells from patients having aPL antibodies without clinical problems; this effect required CD4 ϩ T lymphocytes and class II MHC molecules. 98 In one study, the ability of IgG to stimulate monocyte tissue factor expression was associated with the presence of decreased free protein S and increased prethrombotic markers. 99,100 Another means by which aPL antibodies may increase tissue factor activity and resultant Xa generation is via antibody-mediated inhibition of tissue factor pathway inhibitor activity.…”
Section: Induction Of Tissue Factor Activity By Leukocytesmentioning
confidence: 98%